(untitled) (Nigerian Journal of Technology, 2018)
The optimal process conditions for the preparation of activated carbon from bean husk were investigated in this study. Four chemical activating agents; potassium hydroxide (KOH), sulphuric acid (H2SO4), zinc chloride (ZnCl2), and ortho-phosphoric acid (H3PO4) were used to activate the carbon. The influence of these agents on the surface area and porosity of activated carbon was determined. The Iodine numbers of 894.65, 1027.69, 1218.24 and 1256.31mg/g were found for the KOH, H2SO4,ZnCl2 and H3PO4activated carbons respectively. This indicates that the one prepared using ortho- phosphoric acid (H3PO4) produced the best activated carbon. The influence of activation temperature was studied between 500oC and 900oC. The effect of activation temperature shows an optimum temperature of 700oC at the time of 30mins. Further studies revealed that the best impregnation ratio of carbon to ortho-phosphoric acid was 10:5as it gave a maximum iodine number of 1288.926.The results of the characterization show that the values of apparent density, ash content, moisture content and pH of the activated carbon fall within the range recommended by ASTM. This activated carbon is suitable for the treatment of effluent water and gases. http://dx.doi.org/10.4314/njt.v37i3.17